Brain Activation by H1 Antihistamines Challenges Conventional View of Their Mechanism of Action in Motion Sickness: A Behavioral, c-Fos and Physiological Study in Suncus murinus (House Musk Shrew) - Tu, Longlong; Lu, Zengbing; Dieser, Karolina; Schmitt, Christina; Chan, Sze Wa; Ngan, Man P.; Andrews, Paul L. R.; Nalivaiko, Eugene; Rudd, John A. (Frontiers in Physiology, 2017)
Motion sickness occurs under a variety of circumstances and is common in the general population. It is usually associated with changes in gastric motility, and hypothermia, which are argued to be surrogate markers for nausea; there are also reports that respiratory function is affected. As laboratory rodents are incapable of vomiting, Suncus murinus was used to model motion sickness and to investigate changes in gastric myoelectric activity (GMA) and temperature homeostasis using radiotelemetry, whilst also simultaneously investigating changes in respiratory function using whole body plethysmography. The anti-emetic potential of the highly selective histamine H1 receptor antagonists, mepyramine (brain penetrant), and cetirizine (non-brain penetrant), along with the muscarinic receptor antagonist, scopolamine, were investigated in the present study. On isolated ileal segments from Suncus murinus, both mepyramine and cetirizine non-competitively antagonized the contractile action of histamine with pKb values of 7.5 and 8.4, respectively; scopolamine competitively antagonized the contractile action of acetylcholine with pA2 of 9.5. In responding animals, motion (1 Hz, 4 cm horizontal displacement, 10 min) increased the percentage of the power of bradygastria, and decreased the percentage power of normogastria whilst also causing hypothermia. Animals also exhibited an increase in respiratory rate and a reduction in tidal volume. Mepyramine (50 mg/kg, i.p.) and scopolamine (10 mg/kg, i.p.), but not cetirizine (10 mg/kg, i.p.), significantly antagonized motion-induced emesis but did not reverse the motion-induced disruptions of GMA, or hypothermia, or effects on respiration. Burst analysis of plethysmographic-derived waveforms showed mepyramine also had increased the inter-retch+vomit frequency, and emetic episode duration. Immunohistochemistry demonstrated that motion alone did not induce c-fos expression in the brain. Paradoxically, mepyramine increased c-fos in brain areas regulating emesis control, and caused hypothermia; it also appeared to cause sedation and reduced the dominant frequency of slow waves. In conclusion, motion-induced emesis was associated with a disruption of GMA, respiration, and hypothermia. Mepyramine was a more efficacious anti-emetic than cetirizine, suggesting an important role of centrally-located H1 receptors. The ability of mepyramine to elevate c-fos provides a new perspective on how H1 receptors are involved in mechanisms of emesis control.